2017
DOI: 10.1038/s41598-017-14678-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gas sorption-induced swelling/shrinkage on the cleat compressibility of coal under different bedding directions

Abstract: The cleat compressibility of coal is a key parameter that is extensively used in modeling the coal reservoir permeability for Coal Bed Methane (CBM) recovery. Cleat compressibility is often determined from the permeability measurement made at different confining pressures but with a constant pore pressure. Hence, this parameter ignores the sorption strain effects on the cleat compressibility. By using the transient pulse decay (TPD) technique, this study presents the results from a laboratory characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Most of the coal permeability models include several key parameters to describe the physical and mechanical properties of the coal, including typically Poisson's ratio (ν), modulus of elasticity (E), porosity (ϕ), swelling and strain coefficients (ε L and β), and cleat compressibility (C f ). Commonly, the cleat compressibility is found by regression of the model to measured permeability data (k) , Peng, et al 2017, Zheng, et al 2012. A more useful approach would be to determine cleat compressibility independently since a primary objective in many cases is to predict permeability, rather than use it as a measured value to extract coal properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Most of the coal permeability models include several key parameters to describe the physical and mechanical properties of the coal, including typically Poisson's ratio (ν), modulus of elasticity (E), porosity (ϕ), swelling and strain coefficients (ε L and β), and cleat compressibility (C f ). Commonly, the cleat compressibility is found by regression of the model to measured permeability data (k) , Peng, et al 2017, Zheng, et al 2012. A more useful approach would be to determine cleat compressibility independently since a primary objective in many cases is to predict permeability, rather than use it as a measured value to extract coal properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Injection of pure CO 2 into coal seams usually has a negative effect—coal swelling‐induced permeability decreasing, due to the greater adsorption affinity of CO 2 to coal than of CH 4 . Related studies show that CO 2 injections will cause a reduction in coal permeability by nearly two orders of magnitude, especially near the injection well .…”
Section: Introductionmentioning
confidence: 99%
“…25 Injection of pure CO 2 into coal seams usually has a negative effect-coal swelling-induced permeability decreasing, due to the greater adsorption affinity of CO 2 to coal than of CH 4 . 5,[25][26][27] Related studies show that CO 2 injections will cause a reduction in coal permeability by nearly two orders of magnitude, especially near the injection well. 9,12,15 Even if the CO 2 -ECBM is completed, the decreased coal permeability cannot rebound to initial values, thus results in the deterioration of well injectivity.Another gas injected into coal seams is N 2 , which has a different mechanism of ECBM recovery than CO 2 .…”
mentioning
confidence: 99%
“…This interacts quite strongly with the coal and may increase the cleat compressibility by softening the coal material. Peng, et al (2017) showed in a study with coals from the Qinshui Basin that cleat compressibility factors determined from CO2 core flooding experiments were much higher than cleat compressibility factors determined from CH4 core flooding experiments, as shown in Table 4-4.…”
Section: Equation 4-9mentioning
confidence: 87%
“…Most of the coal permeability models include several key parameters to describe the physical and mechanical properties of the coal, including typically Poisson's ratio (ν), modulus of elasticity (E), porosity (ϕ), swelling and strain coefficients (εL and β), and cleat compressibility (Cf). Commonly, the cleat compressibility is found by regression of the model to measured permeability data (k) (Zheng, et al 2012, Peng, et al 2017. A more useful approach would be to determine cleat compressibility independently since a primary objective in many cases is to predict permeability, rather than use it as a measured value to extract coal properties.…”
Section: Introductionmentioning
confidence: 99%